1993
DOI: 10.1128/aem.59.7.2022-2028.1993
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of sulfites, temperature, and agitation time on production of glycerol in grape juice by Saccharomyces cerevisiae

Abstract: Analysis of variance was used to evaluate the simultaneous effects of strain, incubation temperature (15 to 25°C), agitation time (0 to 24 h), and initial sulfite concentration (100 to 300 ppm) on glycerol production in grape juice by Saccharomyces cerevisiae. Fourteen strains were studied to determine their growth patterns in the presence of sulfites and ethanol. Baker's yeast strains were more sensitive to sulfite than wine strains, and little growth occurred at initial sulfite levels greater than 150 ppm. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 7 publications
2
26
0
2
Order By: Relevance
“…Glycerol production by yeast is influenced by many growth and environmental factors (Albers et al, 1996;Remize et al, 2000). Several studies have shown that an increase in temperature resulted in higher glycerol production (Gardner et al, 1993;Remize et al, 2000). It is reported that the optimum temperature for maximum glycerol production by commercial wine yeast strains of S. cerevisiae varies between 22°C and 32°C (Scanes et al, 1998).…”
Section: Glycerol Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycerol production by yeast is influenced by many growth and environmental factors (Albers et al, 1996;Remize et al, 2000). Several studies have shown that an increase in temperature resulted in higher glycerol production (Gardner et al, 1993;Remize et al, 2000). It is reported that the optimum temperature for maximum glycerol production by commercial wine yeast strains of S. cerevisiae varies between 22°C and 32°C (Scanes et al, 1998).…”
Section: Glycerol Concentrationmentioning
confidence: 99%
“…Glycerol is the most abundant by-product of wine fermentation after ethanol and carbon dioxide. This polyalcohol does not directly contribute to wine aroma due to its nonvolatile nature, but it contributes to sweetness, fullness and smoothness (Gardner et al, 1993;Remize et al, 2000;Taherzadeh et al, 2002). Typical glycerol levels in wine are given as 1-15 g L )1 , with average values approximately 7 g L )1 (Taherzadeh et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For a given starting juice, this footprint can change due to the yeast strain used or the environmental conditions of the fermentation. Previous studies have shown that different S. cerevisiae wine yeast strains fermenting the same juice under identical conditions can yield very different wines due to differences in the metabolic footprint (Gardner et al, 1993;Romano et al, 1994Romano et al, , 2003Benitez et al, 1996;Mortimer, 2000;Remize et al, 2000;Torrea & Ancin, 2002;Fleet, 2003). However, most of these studies compared only a small number of yeast (< 10) and/or a small number of metabolites (< 20), often in synthetic must or media, thereby not giving a true representation of a grape fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the favourable impact on wine quality, glycerol production is one of the desir-able features in wine yeast selection. Glycerol production by yeast is affected by many growth and environmental factors (Gardner et al 1993;Remize et al 2000). This metabolite is synthesized by yeasts in response to a hyperosmotic medium.…”
Section: Introductionmentioning
confidence: 99%